THE CONCEPT OF SUCCESS IN MODERN SOCIETY - Ganieva Dilshoda Izzatulla kizi; Salimmurodova Intizor Siroj kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Success is broadly considered one of the most important goals in people’s lives. However, the notion of success is sophisticated and can be interpreted in various ways depending on individual values, cultural background, and social expectations. This article aims to explore the meaning of success and identify the key factors that contribute to achieving it. By analyzing previous studies and theoretical perspectives, the paper shows that success cannot be determined only by financial gain or professional status. Instead, it also includes personal fulfillment, emotional well-being, and the ability to maintain meaningful and valuable relationships. The findings suggest that perseverance motivation, and continuous personal development are indispensable components of long-term success.